Pembentukan Citra Diri Remaja Kristen Melalui Pendidikan Kristiani - Sadrakh Sugiono; Yudiahline Ruthasye Sodak (EPIGRAPHE: Jurnal Teologi dan Pelayanan Kristiani, 2023)
The adolescent period is a critical phase in an individual's self-image development, signifying not only a transition from childhood to adolescence. Self-image encompasses one's self-perception and evaluation, wielding influence over various facets of life, including behavior, emotional well-being, and social interactions. Factors like parental upbringing, peer relationships, and educational guidance contribute significantly to the formation of adolescent self-image. This research investigates the impact of Christian religious education on the shaping of self-image in Christian adolescents, utilizing a qualitative descriptive approach. The results highlight the pivotal role of Christian religious education, emphasizing instructional materials focused on Christology, Christian anthropology, and soteriology in molding adolescent self-image. The implications of these findings provide valuable guidance and recommendations for Christian educators, churches, and communities to develop more effective and comprehensive religious education programs. These programs will assist Christian adolescents in cultivating a robust and positive self-image firmly rooted in their faith.